Ethnomedicinal Plants of Kotia Hills of Vizianagaram District, Andhra Pradesh, India - and M. Venkaiah, N. Chandra Babu*, M.Tarakeswara Naidu (Journal of Phytology, 2010)
An ethnomedicinal study was carried out on the tribals of Kotia Hills of Vizianagaram district, Andhra Pradesh, to document the plants used in various ailments. A total of 62 plant species belonging to 41 families were recorded. Majority of the plant species described in the present paper was used in the snakebite, diarrhoea, rheumatoid arthritis, bone fracture, asthma and malaria. Most of the herbal remedies were taken externally in the form of paste. All these plants and plant parts need to be evaluated through phyto and pharmacochemical investigations to discover their potentiality as drugs. There is an urgent need to explore and document the ethnomedicinal plants used by the tribals of Kotia Hills before such valuable knowledge vanishes. Key words: Ethnomedicine, Ethnomedicinal plants, Kotia Hills tribes, Vizianagaram district <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no;" lang="EN-SG">N. Chandra Babu et al. Ethnomedicinal Plants of Kotia Hills of Vizianagaram District, Andhra Pradesh, India. J Phytol 2/6 (2010) 76-82.